Cyber-Physical Systems: Challenges and Future Directions (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Cyber-Physical Systems (CPS) integrate computational algorithms with physical components, enabling advanced functionalities in various domains. This paper explores the challenges and future directions of CPS, focusing on security, safety, privacy, and interoperability. In terms of security, CPS face threats to confidentiality, integrity, and availability, necessitating advancements in intrusion detection, prevention systems, and secure communication protocols. Safety improvements include predictive maintenance and autonomous decision-making systems to enhance reliability and resilience. Privacy-enhancing techniques like anonymization and user-centric controls are crucial for data protection. Interoperability solutions, such as middleware and semantic frameworks, facilitate seamless integration among heterogeneous CPS components. Future directions involve leveraging machine learning and AI for security, integrating digital twins for predictive maintenance, and enhancing user-centric privacy controls. These advancements are vital for the continued development and adoption of CPS in diverse applications.